Cognitive, Emotional and Methodological Aspects of Musician-Performer’s Thinking - Vitalіi ZAIETS; Oksana ZAIETS; Oleksandr BENZIUK; Oleksandr LIHOTSKYI (Studia Universitatis Babeş-Bolyai. Musica, 2025)
SUMMARY. The way of thinking of a performing musician is a complex and multifaceted process that combines rational, intuitive, and emotional aspects. It not only ensures the effectiveness of performing activities, but also determines the artistic depth and individuality of the interpretation of a musical work. Understanding the specifics of performing thinking is important for the formation of a musician’s professional skills as it is carried out through mental processes, interaction with musical material, interpretation of the composer’s idea and emotional and aesthetic connection with the listening audience. The relevance of the study is based on the need for a comprehensive understanding of these aspects in the context of modern performing practice, which allows not only to deepen the theoretical understanding of the specifics of performing thinking, but also to develop practical recommendations for improving the professional skills of musicians.